Relationships between anthocyanins and other compounds and sensory acceptability of Hibiscus drinks - Bechoff, Aurelie; Cisse, Mady; Fliedel, Geneviève; Declemy, Anne-Laure; Ayessou, Nicolas; AKISSOE, H. NOËL; Touré, Cheikh; Bennett, Ben; Pintado, Manuela; Pallet, Dominique; Tomlins, Keith I (My University, 2014)
Chemical composition of Hibiscus drinks (Koor and Vimto varieties, commercial and traditional, infusions and syrups) (n = 8) was related to sensory evaluation and acceptance. Significant correlations between chemical composition and sensory perception of drinks were found (i.e. anthocyanin content and Hibiscus taste) (p < 0.05). Consumers (n = 160) evaluated drink acceptability on a 9-point verbal hedonic scale. Three classes of behaviour were identified: (a) those who preferred syrup (43% of consumers); (b) those who preferred infusion (36%); and (c) those who preferred all of the samples (21%). Acceptability of ‘syrup likers’ was positively correlated to sweet taste, reducing sugar content and inversely correlated to acidic taste and titratable acidity (p < 0.10). Acceptability of ‘infusion likers’ was positively correlated to the taste of Hibiscus drink and anthocyanin content. The study showed that the distinctions between the acceptability groups are very clear with respect to the chemical composition and rating of sensory attributes.
Keywords: Hibiscus sabdariffa L.; Roselle; Cluster; Sensory tasting; Acceptability; Syrup; Infusion